Impact of “Lateralizing” the Sigmoid Colostomy on Port Ergonomics in Laparoscopic Anorectoplasty for High Anorectal Malformations - Agrawal, Vikesh; Sulya, Deepak; Acharya, Himanshu; Tiwari, Abhishek; Sharma, Dhananjaya (European Journal of Pediatric Surgery, 2020)
Introduction The high-type anorectal malformations (ARM) are conventionally managed by an initial left iliac fossa sigmoid colostomy, followed by laparoscopic anorectoplasty (LARP). Such a stoma occupies left half of the infraumbilical region and hinders the LARP ergonomics, leading to the surgeon's discomfort. We studied the outcome and impact of “lateralizing” (shifting laterally in the abdominal wall) the colostomy on port ergonomics.Materials and Methods This prospective study was conducted in the pediatric surgery unit of a medical college in central India between March 2014 and June 2017 in two parts. In the first part of the study, neonates with high ARM were block randomized in two groups: conventional colostomy (CC) in left iliac fossa and lateral colostomy (LC, laterally placed abdominal colostomy). Outcomes of colostomy were compared among these two groups. In the second part of the study, 40 consecutive infants from both types of colostomy groups underwent ergonomic comparison and assessment of the surgeon's discomfort during LARP (CC-LARP and LC-LARP). Standard statistical tests were used for comparison.Results In the first part of the study, 203 ARM cases were included in this study; 100 underwent CC and 103 underwent LC. Colostomy prolapse, excoriation, reversed stoma, and short distal limb were significantly higher in the CC group. In the second part of the study, the LC-LARP group showed many significant advantages over the CC-LARP group, including less peri-stomal adhesions, better vision, shorter operative time, and better ergonomics (better manipulation, elevation, and azimuth angles). The LC-LARP also significantly reduced the surgeon's discomfort.Conclusion Lateralization of high-sigmoid colostomy should be preferred over left iliac fossa sigmoid colostomy for ARM, as it improves the port ergonomics and reduces the surgeon's discomfort for second stage LARP.
Keywords: anorectal malformations; sigmoid colostomy; complications; laparoscopic anorectoplasty; ergonomics